Transcriptome analysis reveals the molecular mechanism of differences in growth between photoautotrophy and heterotrophy in Chlamydomonas reinhardtii - Chen, Jing; Chen, Yuanhao; He, Weiling; Liang, Honghao; Hong, Ting; Li, Tangcheng; Du, Hong (Frontiers in Plant Science, 2024)
The green alga Chlamydomonas reinhardtii can grow photoautotrophically utilizing light and CO2, and heterotrophically utilizing acetate. The physiological and biochemical responses of autotrophy and heterotrophy are different in C. reinhardtii. However, there is no complete understanding of the molecular physiology between autotrophy and heterotrophy. Therefore, we performed biochemical, molecular and transcriptome analysis of C. reinhardtii between autotrophy and heterotrophy. The cell growth characterization demonstrated that heterotrophic cell had enhanced growth rates, and autotrophic cell accumulated more chlorophyll. The transcriptome data showed that a total of 2,970 differentially expressed genes (DEGs) were identified from photoautotrophy 12h (P12h) to heterotrophy 12h (H12h). The DEGs were involved in photosynthesis, the tricarboxylic acid cycle (TCA), pyruvate and oxidative phosphorylation metabolisms. Moreover, the results of qRT-PCR revealed that the relative expression levels of malate dehydrogenase (MDH), succinate dehydrogenase (SDH), ATP synthase (ATPase), and starch synthase (SSS) were increased significantly from P12h and H12h. The protein activity of NAD-malate dehydrogenase (NAD-MDH) and succinate dehydrogenase (SDH) were significantly higher in the H12h group. The above results indicated that the high growth rate observed in heterotrophic cell may be the effects of environmental or genetic regulation of photosynthesis. Therefore, the identification of novel candidate genes in heterotrophy will contribute to the development of microalga strains with higher growth capacity and better performance for biomass production.